Scenario simulation for bioeconomic evaluation in stocker-finish in beef cattle grazing systems in South Brazil (Research, Society and Development, 2021)
The aim of this study was to evaluated twenty-seven scenarios simulated in stocker-finishing beef cattle grazing systems, performed with real data and the aid of integrated Microsoft Excel® spreadsheets. The scenarios, consisted of three intensification levels (management modules): low (native pastures - NP), intermediate (NP + winter pasture – WP) and high (NP + WP + summer pasture – SP); three animal categories: calf, steer and cow; and three commercial arrangements, differing in the purchase and sale prices of animals: high/low (unfavorable), medium/medium (medium) and low/high (favorable). With unfavorable prices only the calf responded positively to the increasing level of system intensification, while steer and cow lost margin when the system was intensified with SP compared to the intermediate level. Between categories, the cow has negative margins at all intensification levels, the steer has the best margin at low and intermediate levels, and the calf at high level. In the context of average prices, the cow continues to decrease its margin due to intensification with SP. However, it obtains positive results in all management modules. In this case, the steer shows increasing gains with system intensification, demonstrating better performance than the calf in all management modules. In favorable price situations, all categories show increasing gains per area as the system intensifies. At this juncture, at an intermediate intensification level, the cow has the best performance per area between categories, while at low and high levels the steer responds with the best margin. When assessing the margin/head/year, in any commercial and animal category, intensification with SP loses competitiveness in relation to the intermediate intensification management module. However, when the margin/area was evaluated, only 3 of 27 scenarios decreased the margin.